Breast carcinoma grading on core needle biopsy – to grade or not to grade? - Szpor, Joanna; Witczak, Karolina; Storman, Monika; Streb-Smoleń, Anna; Krzemień, Agnieszka; Okoń, Krzysztof; Hodorowicz-Zaniewska, Diana; Streb, Joanna (Polish Journal of Pathology, 2023)
Core needle biopsy (CNB) is well established as an important diagnostic tool in diagnosing breast cancer and it is now considered the initial method of choice for diagnosing breast disease and the basis for the treatment planning. The concordance rate between CNB and surgical excision specimen in determination of histological grade (HG) varies widely across literature, ranging from 59-91%. The aim of our study was to investigate the level of concordance between CNB and surgical excision specimen for the determination of HG for breast cancer patients. The study population included 157 women with a breast tumor who underwent a core needle biopsy for breast carcinoma and a subsequent surgical excision of the tumor. The concordance level between core needle biopsy and surgical resection specimen for overall histologic grading was 73%: for tubule formation – 71%, for nuclear pleomorphism – 91%, for the mitotic index – 59%. Our study shows that our institution’s histologic grading of CNBs and surgical excisions shows a fairly good correlation and is useful for the planning of treatment.